2005
DOI: 10.1080/135485005123315407
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal depressive mood in Turkish women

Abstract: The aim of this study was measure the prevalence and influencing factors of depressive mood after delivery. We performed this study on 912 women who gave birth at Maternity Hospital in Bursa/ Turkey. We used Zung's Self-Rating Depression Scale (ZSDS) and a questionnaire in order to obtain the women's backgrounds and the possible risk factor characteristics. The ZSDS and questionnaire were filled out within 1 week after the delivery, by means of face-to-face interviews at the hospital, and 1 month after deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
1
7
1
Order By: Relevance
“…This study found that first-time mothers had higher depression scores than did multiparous mothers. Previous research findings do not show a consistent pattern in number of children with one Turkish study showing no relationship between parity and depression (Ozdemir, Ergin, Selimoglu, & Bilgel, 2005) and another Turkish study showing an increase of children leading to higher depression scores (Danaci et al, 2002). No study seems to show higher rates for first-time mothers and yet one could postulate this is the most difficult birth since the mother is entering an unknown emotional and physical world.…”
Section: Discussionmentioning
confidence: 90%
“…This study found that first-time mothers had higher depression scores than did multiparous mothers. Previous research findings do not show a consistent pattern in number of children with one Turkish study showing no relationship between parity and depression (Ozdemir, Ergin, Selimoglu, & Bilgel, 2005) and another Turkish study showing an increase of children leading to higher depression scores (Danaci et al, 2002). No study seems to show higher rates for first-time mothers and yet one could postulate this is the most difficult birth since the mother is entering an unknown emotional and physical world.…”
Section: Discussionmentioning
confidence: 90%
“…Other studies have reported no such influence in developed countries (Boyce and Hickey, 2005;Green et al, 2006;Kim et al, 2008;Leigh and Milgrom, 2008;Hamdan and Tamim, 2011;Goker et al, 2012;Deng et al, 2014). In developing countries, low socio-economic status is a risk factor for postpartum depression Ahmed et al, 2012;Ozdemir et al, 2014). Low education level (Ege et al, 2008;Kheirabadi et al, 2009;Yagmur and Ulukoca, 2010;Goker et al, 2012;Ozdemir et al, 2014), low income Moraes et al, 2006;Andajani-Sutjahjo et al, 2007;Dindar and Erdogan, 2007) and unemployment (Kheirabadi et al, 2009) are associated with postpartum depression.…”
Section: Socio-demographic Factorsmentioning
confidence: 92%
“…In developing countries, contradictory findings related to obstetric and pediatric factors were reported only for mode of delivery (Alami et al, 2006;Yagmur and Ulukoca, 2010;Ahmed et al, 2012;Barbadoro et al, 2012), parity (Abiodun, 2006;Alami et al, 2006;Ayvaz et al, 2006;Csatordai et al, 2007;Ho-Yen et al, 2007;Xie et al, 2007;Yagmur and Ulukoca, 2010;Goker et al, 2012;Ozdemir et al, 2014) and sex of baby (Ayvaz et al, 2006;Moraes et al, 2006;Nakku et al, 2006;Dindar and Erdogan, 2007;Xie et al, 2007;Ali et al, 2009;Yagmur and Ulukoca, 2010;Xie et al, 2011). The preference to the sex of the baby changes according to culture.…”
Section: Obstetric and Pediatric Factorsmentioning
confidence: 94%
See 1 more Smart Citation
“…A repeated measure analysis of variance (RM ANOVA) was used to compare the EPDS scores between women with and without severe maternal morbidity at 1 and 6 months postpartum while controlling for potential confounders. The confounders identified in previous research were social support (Eastwood, Jalaludin, Kemp, Phung, & Barnett, ; Yagmur & Ulukoca, ), physical health (Barbadoro et al, ; Gaillard, Le Strat, Mandelbrot, Keïta, & Dubertret, ), occupation (Kheirabadi et al, ), and education (Ozdemir, Ergin, Selimoglu, & Bilgel, ). Age was identified as significant at the univariate level.…”
Section: Methodsmentioning
confidence: 99%